2018
DOI: 10.3390/educsci8030146
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Religion in Religion Education: Notes from the South African Periphery

Abstract: Scholars of Religion Education (RE) have promoted a non-confessional approach to the teaching of religions that explores and examines the religious history of humankind, with due attention paid to its complexity and plurality. In this promotion, the public representation of religion and its impact on RE has not received sufficient attention. An often hegemonic representation of religion constitutes an important part of religion in public life. Moreover, this article argues that this representation is a phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…20 of 2003 on the National Education System, whose national education aims to shape students into human beings who are capable, creative, noble character, order to God, and become good citizens (Dewi & Alam, 2020). Tayob's (2018) elaboration showed that religion is an essential factor in the survival of society and the state. The existence of government policies to provide religious subjects and develop religion in schools dismisses secularisation in education.…”
Section: Discussionmentioning
confidence: 99%
“…20 of 2003 on the National Education System, whose national education aims to shape students into human beings who are capable, creative, noble character, order to God, and become good citizens (Dewi & Alam, 2020). Tayob's (2018) elaboration showed that religion is an essential factor in the survival of society and the state. The existence of government policies to provide religious subjects and develop religion in schools dismisses secularisation in education.…”
Section: Discussionmentioning
confidence: 99%
“…The post-racial and post-mono-religious state thus authorizes the flourishing of religion in both state and private affairs in surprising and unexpected ways in an attempt to 'turn diversity from an obstacle to nationalism into a national resource, seeking not uniformity but unity' (Chidester 2012: 2). The outcome is a tension between 'political secularism and … a proliferation of religious representations' that are authorized in public life (Tayob 2018). For example, in constitutional court hearings over the practice of minority (non-Christian) religious observance in schools, school and parent-teacher bodies' attempts to mobilize particular Christian definitions of religion are rejected by the court as contravening the constitutional right to religious freedom (Tayob 2017).…”
Section: Religious Nationalism In a Post-apartheid Neoliberal Momentmentioning
confidence: 99%
“…Revell (2008) discusses how numerous difficulties RE encounters in representing religious traditions are linked to the evolution of RE in education policy, which led to a narrow curriculum that typically misrepresents religions as static, monolithic and benign. She argues, along with Erricker (2001) and Tayob (2018), that representations of religions in RE are influenced by a country's lingering dominant public representation of religion. Revell (2008) and Nesbitt (2004, p. 141) notice that 'religion as a unified system of belief and practice dominates in religious education'.…”
Section: Challenges To the Authentic Representation Of Religious Tradmentioning
confidence: 99%
“…The education policy context of the paper is England and Wales, though the themes raised are wider ranging (see for example, Tayob 2018). The type of RE discussed in this paper is secular, multi-faith RE that is a compulsory curriculum subject in non-faith schools in England and Wales.…”
Section: Introductionmentioning
confidence: 99%